A review of human carcinogens. Part E: personal habits and indoor combustions (Lyon, 2012)
"This Volume 100E covers Personal Habits and Indoor Combustions, specifically Tobacco Smoking, Second-hand Tobacco Smoke, Smokeless Tobacco, N'-Nitrosonornicotine and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, Betel Quid and Areca Nut, Consumption of Alcoholic Beverages, Chinese-style Salted Fish, and Indoor Emissions from Household Combustion of Coal.